EFEKTIFITAS PEMBELAJARAN DARING DENGAN E-MODUL TERINTEGRASI GOOGLE EDUCATION PADA MATA PELAJARAN MATEMATIKA KELAS VIII - Darwin Djeni; Jamiatun Nasikhah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
Student interest in class VII SMP NAMIRA Kota Probolinggo on subject Mathematics is classified as low, especially when the subject mathematics fells like it’s always being skipped. This is an accordance with the results of diagnostic Assesment and learning interest of 60 students, the percentage of high interest in learning Mathematics subject, only 30 %. Mathematics is a subject that is considered difficult. It is a challenge to present on pandemic or daring of learn it in an must attractive, easy and fun away. Solution to overcome this problem is through the implementation of google education integrated e-book. The purpose os this study was to determine effectivity of implementation of google education integrated e-book on class VII SMP NAMIRA Kota Probolinggo. The research method used is Mathematics Realistic integrated discovery learning that present on e book. E-book that created with Bookcreator application mix google education. Data collection techniques used were test of students understanding, attitude assessment, observation (quisoner), reflection learning of Mathematics. The results showed that the implementation of google education integrated e book is effective with interest Matematics subject increasing 55,6% on the first meet, the second meet to be 83% . Students learning outcomes describe student interest to follow learning of Mathematics, it is shown assignment collection and result show 10 % under KKM Mathematics subject. Keywords: e-book, Bookcreator, Google Education, FAAST